2015
DOI: 10.1523/jneurosci.2630-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

Bridging Cytoarchitectonics and Connectomics in Human Cerebral Cortex

Abstract: The rich variation in cytoarchitectonics of the human cortex is well known to play an important role in the differentiation of cortical information processing, with functional multimodal areas noted to display more branched, more spinous, and an overall more complex cytoarchitecture. In parallel, connectome studies have suggested that also the macroscale wiring profile of brain areas may have an important contribution in shaping neural processes; for example, multimodal areas have been noted to display an elab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
100
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 134 publications
(113 citation statements)
references
References 30 publications
13
100
0
Order By: Relevance
“…For example, our results support the fact that the primary motor cortex has a very specific anatomical organization, which reacts in a unique manner to the stimulation, potentially due to the absence of cortical layer IV and to the presence of the large cortico-spinal pyramidal neurons. Furthermore, the pyramidal neurons of layer V are particularly large in the motor/premotor areas and in the median part of the occipital lobe (van den Heuvel et al, 2015), where we also observed the greatest early LSA (from 15 to 45ms, see Fig. 4b).…”
Section: Functional Cytoarchitectonicssupporting
confidence: 59%
See 1 more Smart Citation
“…For example, our results support the fact that the primary motor cortex has a very specific anatomical organization, which reacts in a unique manner to the stimulation, potentially due to the absence of cortical layer IV and to the presence of the large cortico-spinal pyramidal neurons. Furthermore, the pyramidal neurons of layer V are particularly large in the motor/premotor areas and in the median part of the occipital lobe (van den Heuvel et al, 2015), where we also observed the greatest early LSA (from 15 to 45ms, see Fig. 4b).…”
Section: Functional Cytoarchitectonicssupporting
confidence: 59%
“…In humans, indirect evidence between brain dynamics and cytoarchitectonics from post-hoc correlation analysis of cortical maps has been suggested from analysis of resting state functional MRI spectral properties (Song et al, 2014). A significant association between cytoarchitectonic features of human cortical organization, in particular the size of layer 3 neurons, and whole-brain cortico-cortical connectivity has been recently identified, and suggests existing relationships between microscale cytoarchitectonics and macroscale connectomics (van den Heuvel et al, 2015). Because knowing how cytoarchitectonics influence brain dynamics is of outmost importance to increase our understanding of brain functioning, for example by developing more biologically grounded neuronal models in silico (Roy et al, 2014), we develop here a new experimental method using transcranial magnetic stimulation (TMS) to map the dynamical properties of human local cortical microcircuits non invasively.…”
Section: Introductionmentioning
confidence: 99%
“…Since brain hubs tend to have more metabolically costly functional connections, they are likely to be more susceptible to disorders47.Thus, the alteration of such hubs may lead to deficient information flow and the domain of impairments characteristic of CD, such as empathy and perception of others’ feelings5152. The relocation of hubs in CD patients, relative to HCs, on the other side, might reflect the histologically defined variations of these regions during one’s early development, since regions with high degree had greater dendritic branching of pyramidal neurons and larger-size neurons in certain area (cortical layer III), as well as more dendritic spines53. This is consistent with the claim that regional gray matter volume is substantially associated with regional network centrality54.…”
Section: Discussionmentioning
confidence: 99%
“…However, mounting evidence suggests that genetic/epigenetic variation in OXTR may specifically contribute to individual differences in social-behavioral phenotypes by modulating the functional neuroanatomy of a number of brain regions 83 . Such a mechanism is supported by recent work showing that cellular-level networks display similar organization to macroscale cortical networks 129 . Thus, the cytoarchitectural effects of genetic/epigenetic variation may cascade upwards to large-scale functional network organization.…”
Section: Implications For Oxytocin Action and Social Behaviormentioning
confidence: 68%
“…We have discussed a role for oxytocin in modulating processes such as LTP, but more broadly, there is evidence to suggest that oxytocin initiates and fosters coherent activity across neural networks-both at the cellular level and macroscopic cortical level 7,128 . Indeed, if cellular systems are not firing together (and consequently not wiring together), we would expect this level of disconnection to cascade upwards into higher-level networks, and recent evidence suggests this is true for human brain systems 129 . It is therefore unsurprising that ASD phenotypes are commonly associated with hypoconnectivity and generally "noisy brains" [130][131][132] .…”
Section: Social Cognition Is An Inferential Processmentioning
confidence: 99%